2016
DOI: 10.1177/0886260516635318
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gender Ideology, Victim Resistance, and Spiking a Drink on Acquaintance Rape Attributions

Abstract: The current study examined observer's attributions about the victim and perpetrator of an alleged acquaintance rape. Participants included 504 college students from a public university in the northeastern United States who read a brief crime report and completed a series of questionnaires for course credit. While men tended to attribute more blame to the victim than women, gender ideology emerged as a stronger predictor of rape attributions, and some types of sexist beliefs were associated with greater victim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…Abstinence‐only sex education discourse tends to position sex in this manner by reinforcing messages about maintaining one's “value” by avoiding sex until marriage (particularly for women) . Although sexual double standards are not new, some have argued that contemporary young adults and college students do not endorse these traditional views . Our participants still seem to endorse these cultural norms, which seem, in turn, to influence consent communication.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Abstinence‐only sex education discourse tends to position sex in this manner by reinforcing messages about maintaining one's “value” by avoiding sex until marriage (particularly for women) . Although sexual double standards are not new, some have argued that contemporary young adults and college students do not endorse these traditional views . Our participants still seem to endorse these cultural norms, which seem, in turn, to influence consent communication.…”
Section: Discussionmentioning
confidence: 76%
“…Researchers have not explicitly examined the extent to which these gender and cultural norms influence consent communication among college students. Thus, despite the extensive work examining sexual double standards, an exploratory analysis in the context of consent communication would be fruitful.…”
mentioning
confidence: 99%
“…It has been found that jurors ignore lack of consent if wantedness is present (McHugh, 1996). This is further evidence that suggests it is vital to understand laypersons' perceptions of sexual assault because they are the ones present when it happens, contribute to victimization of survivors of sexual assault, responses to victims and jury decision making (Angelone, Mitchell, & Smith, 2014). plementary table S2) for Experiment 2 highlighting the category, a description and how it is used across conditions, and the number of mentions in the participants responses in their reasons for appraising situations as rape or not These mentions include participants stating that the presence or absence of the category mattered and whether the category was relevant to their decision Top value in each cell represents the subject position and the bottom value represents the initiator position Condition labels are C consent, W wanted, P pleasurable (with a lowercase n indicating it wasn't included in the vignette) The use of additional information in judging whether scenarios represent rape and some of the comments made indicate rape myths and victim blaming were present in our student sample (e.g., Aosved & Long, 2006;Bohner et al, 2009;Burt, 1980;O'Donohue, Yeater, & Fanetti, 2003): In particular, the myth that forced sex is justified if the victim appears to want sex prior to refusing (Payne, Lonsway, & Fitzgerald, 1999).…”
Section: Discussionmentioning
confidence: 92%
“…The use of hypothetical scenarios has predominantly been adopted in psychology to examine student attitudes regarding topics such as victim perception and blame (e.g. Angelone, Mitchell & Smith, 2016), or to determine the decision-making and perceptions of "would-be" sexual offenders using college student samples (e.g. Bachman, Paternoster & Ward, 1992;Bouffard, 2011), thus limiting the generalizability of the findings.…”
Section: Introductionmentioning
confidence: 99%